(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The White Palace is an architectural monument built by Amir Temur in Shahrisabz. The area of this palace, which is still famous for its luxury and beauty, is a place for tourists. The article presents a landscape design proposal project for the architectural solution of the landscape of the Oksaroy historical monument area.